1986
DOI: 10.1021/bi00364a026
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of iron by gallium in siderophores

Abstract: Siderophores are iron transport compounds produced by numerous microorganisms and which strongly chelate Fe(III), but not Fe(II). Other trivalent metals, such as Al(III), Cr(III), or Ga(III), are not capable of significantly displacing iron from siderophores. However, I demonstrate here that Ga(III) can effectively displace iron under reducing conditions. With ascorbate as reductant and ferrozine as Fe(II) trapping agent, the kinetics of reductive displacement of iron by Ga(III) were followed spectroscopically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 17 publications
0
35
0
4
Order By: Relevance
“…Emery & Hoffer (1980) showed that gallium analogues of siderophores could be taken up by micro-organisms in an active transport process indistinguishable from that of ferri-siderophores. In addition, it has been demonstrated that Ga3+ can displace iron from siderophores under reducing conditions (Emery, 1986). This was confirmed for the reduction of FOB by S. cerevisiae: the rate of formation of the Fe (I1) 1 mwferrozine and 5% (w/v) glucose was increased by more than 50% by the addition of 500 p~-G a ( N 0~)~.…”
Section: Iron Uptake By Rwn-growing Cellsmentioning
confidence: 71%
See 1 more Smart Citation
“…Emery & Hoffer (1980) showed that gallium analogues of siderophores could be taken up by micro-organisms in an active transport process indistinguishable from that of ferri-siderophores. In addition, it has been demonstrated that Ga3+ can displace iron from siderophores under reducing conditions (Emery, 1986). This was confirmed for the reduction of FOB by S. cerevisiae: the rate of formation of the Fe (I1) 1 mwferrozine and 5% (w/v) glucose was increased by more than 50% by the addition of 500 p~-G a ( N 0~)~.…”
Section: Iron Uptake By Rwn-growing Cellsmentioning
confidence: 71%
“…In contrast, Ga3+ had little or no effect. Emery (1986) showed that citrate could inhibit the reductive exchange reaction between Ga3+ and FOB, and that acidic conditions were required for optimum reaction rate. Citrate buffer, pH 6.5, was therefore replaced by acetate buffer, pH 5.2, for studying the effects of Ga3+ and Ga(II1)-DFOB on FOB uptake rate as a function of FOB concentration.…”
Section: Iron Uptake By Rwn-growing Cellsmentioning
confidence: 99%
“…Gallium is an isosteric diamagnetic substitute for Fe(III) [39] and, thus, the affinity constants of many siderophores for gallium are in the range of their iron counterparts. At that time, it was also demonstrated that under reducing conditions, Ga(III) can rapidly displace Fe(III) from siderophores, whereas without concerted reduction of the iron no significant exchange was observed [40]. Emery and Hoffer [41] have used 67 Ga to study the uptake mechanisms for different siderophores in Ustilago sphaerogena and found this energy-dependent process to be indistinguishable from that of its Fe(III) counterpart.…”
Section: Siderophores For Molecular Imaging Of Infectionmentioning
confidence: 99%
“…Genetic studies are also not simple : a mutation that affects some step of nonreductive iron assimilation in S. cerevisiae will be difficult to detect because iron can still enter the cells by the reductive mechanism. Emery (1986) used gallium analogues of siderophores, which cannot be reduced, to distinguish between reductive and non-reductive uptake of siderophores by U. sphaerogena. We used mutants of S. cerevisiae in which the FET3 and FET4 genes, encoding components of the high-affinity and low-affinity reductive uptake systems, respectively (Askwith et al, 1994 ;Dix et al, 1994), had been deleted.…”
Section: Introductionmentioning
confidence: 99%